Experimental Study on the Acceleration Amplification Ratio of Cable Terminations for Electric Power Facilities - Bub-Gyu Jeon; Sung-Jin Chang; Sung-Wan Kim; Dong-Uk Park; Nakhyun Chun (Energies)
Among national infrastructure facilities, electric power facilities are very important sites that must maintain their functions properly even during a natural disaster or during social crises. Therefore, seismic design is required when necessary for major electric power facilities that have a significant impact when damaged in the event of an earthquake. In electric power facilities, bushings are generally installed in devices or structures. Therefore, ground acceleration can be amplified through devices, such as transformers, or sub-structures. Among various electric power facilities, cable terminations are representative cantilever-type substation facilities consisting of a bushing, a sub-structure, and support insulators. The bushings of cable terminations are generally made of porcelain or fiber-reinforced plastic (FRP) materials, and they may have different dynamic characteristics. This study attempted to estimate the acceleration amplification ratio in the main positions of cable terminations considering the materials of bushings. For two cable terminations with different specifications and bushing materials, three-axis shake table tests were conducted in accordance with IEEE 693, which includes a seismic performance evaluation method for a power substation facility. The acceleration amplification ratios at the top of the bushing, mass center, and top of the support structure were estimated using the acceleration responses of each cable termination. They were then compared with the acceleration amplification factors presented in design standards. Consequently, the acceleration amplification ratio of cable termination with an FRP bushing was lower than that of the cable termination with a porcelain bushing.